Metformin is Protective Against the Development of Mood Disorders - Lake, Jacqueline; Bortolasci, Chiara C.; Stuart, Amanda L.; Pasco, Julie A.; Kidnapillai, Srisaiyini; Spolding, Briana; Truong, Trang T. T.; Panizzutti, Bruna; Liu, Zoe S. J.; Dean, Olivia M.; Crowley, Tamsyn; Richardson, Mark; et al. (Pharmacopsychiatry, 2023)
Abstract Introduction Mood disorders are a major cause of disability, and current treatment options are inadequate for reducing the burden on a global scale. The aim of this project was to identify drugs suitable for repurposing to treat mood disorders. Methods This mixed-method study utilized gene expression signature technology and pharmacoepidemiology to investigate drugs that may be suitable for repurposing to treat mood disorders. Results The transcriptional effects of a combination of drugs commonly used to treat mood disorders included regulation of the steroid and terpenoid backbone biosynthesis pathways, suggesting a mechanism involving cholesterol biosynthesis, and effects on the thyroid hormone signaling pathway. Connectivity Map analysis highlighted metformin, an FDA-approved treatment for type 2 diabetes, as a drug having global transcriptional effects similar to the mood disorder drug combination investigated. In a retrospective cohort study, we found evidence that metformin is protective against the onset of mood disorders. Discussion These results provide proof-of-principle of combining gene expression signature technology with pharmacoepidemiology to identify potential novel drugs for treating mood disorders. Importantly, metformin may have utility in the treatment of mood disorders, warranting future randomized controlled trials to test its efficacy.